Trust management in FANET network - Mehenni, Safa; Tahiri, Malika; Chaïb, Noureddine (Laghouat : Université Amar Telidji - Département d'informatique, 2023)
The technological advancement in the critical embedded system, avionic and micro electro mechanical system has paved the path to new fully fledged inter connected multi-UAV system, also acronyms as FANET. FANETs considered as most powerful weapon in military assets as well as in civil applications. Due to its infrastructure less design and wireless nature network some security challenges are code overhead that may caused the network performance degradation. Malicious nodes are capable of degrading the network credibility. In our work we have proposed a mechanism based on a trust management in order to estimate the trust values among flying ad hoc nodes in order to eliminate the presence of malicious nodes caused by security issues in Flying Ad-hoc Networks. To demonstrate the effectiveness of our proposed approach we have used Network Simulator NS2 to demonstrate the entire process into simulated environment.